Pengaruh Kegiatan Marketing terhadap Profitabilitas dan Nilai Perusahaan Properti dan Real Estate di BEI - Sonya, Serenia (Business Accounting Review, 2015)
The purpose of this research was to investigate the influence of marketing activity on profitability and market value in property and real estate companies listed in Indonesia Stock Exchange. This study used 45 property and real estate companies during the period of 2008 until 2013 with total 155 annual reports observed. By using multiple linear regression, the results showed that firm age as the component of marketing activities had positive influence to companiesâ profitability and market value. The marketing expense hd a positive and significant influence on profitability and market value that represented by EPS and Market to Book Ratio. Firm size had negative influence profitability and positive influence to market value tha represented by EPS and TobinsâQ.